DESIGN VIDEO COMPANY PROFILE BASED ON 3D ANIMATION ON MILLENNIUM ICT MEDAN - Syarifah Fadillah Rezky; Fifin Sonat; Junus Sinuraya (INFOKUM, 2022)
Nowadays humans are very dependent on technology, this is what makes technology a necessity for some humans. Social media is a medium that helps to socialize with each other and is done online which allows humans to interact with each other anytime and anywhere. Therefore, social media content is very important in the current era, especially during this pandemic, so the company profile video is very influential to the community, because not everyone knows about Millennium ICT Medan. The presence of social media in digital era marketing can be seen from two sides, namely the social media user side and the promotion side. Design this marketing promotional content to attract customers to know what the author is promoting and encourage (invite) to become customers